Should It Always Be Central? Substitution Effects of Multi-Network Embeddedness on Absorptive Capacity - Xiurui Xu; Shanwu Tian (Systems)
In the knowledge economy, organizations embedded within large network systems enhance their capability to identify, acquire, assimilate, and effectively utilize external knowledge. Given the diversity and complexity of these networks, examining the factors that influence organizational absorptive capacity from a multi-network perspective is both essential and timely. However, how organizations can strategically allocate positions across different networks to enhance absorptive capacity remains unclear. Drawing on social network theory and the knowledge-based view, this study proposes that the relational embeddedness of organizations across networks produces an interactive substitution effect on absorptive capacity. Using a composite database of patent, financial, and organizational data, we annually constructed multiple networks of listed companies in the global automobile and components industry and empirically tested the model through multiple stepwise regression analysis. The results indicate that relational embeddedness in both cooperation and knowledge networks positively affects absorptive capacity; nevertheless, relational embeddedness in knowledge networks can limit the positive effect of cooperation network embeddedness on organizational absorptive capacity. This interaction highlights the substitution effect between different network roles in shaping absorptive capacity.